The effect of bow training on increasing upper limb muscles in adolescent archery athletes - Arfiansyah, Eggy; Ulfi Adela, Via; Rihadi Wicaksono, Surya; Asa Habiburrahman, Fauzan (Health Promotion & Physical Activity, 2025)
Achievement in the sport of archery is determined based on the sum of the scores of arrows shot by an athlete hitting the target. This sport requires full concentration and good muscle endurance to support performance in the competition area. Muscle endurance is also influenced by muscle strength, which can be seen from an archery athlete’s composition of muscle mass. This research aims to determine the influence of bow training on upper arm muscle hypertrophy. This research uses a pre-experimental method with a One-Group Pretest-Posttest approach. The test instrument uses a Seca Body Analyzer and a scale used to measure muscle hypertrophy with a kilogram measuring scale. Participants in this research were 17 archery athletes from Malang City. The results of the research show that based on data analysis, a t-value p-value < 0.05 can be obtained. These results indicate that there is an effect of bow training on muscle mass. Therefore, it can be interpreted that bow training has an effect on arm muscle hypertrophy in adolescent archery athletes in the city of Malang. Based on the results of the research that has been carried out, it can be concluded that there is an influence of bow training on upper arm muscle hypertrophy in adolescent archery athletes in Malang City. This can be used as a guideline in creating a training program during competition preparation for archery athletes.